134 Cladribine: a multicentre long-term efficacy biomarker australian study (CLOBAS). (29th July 2019) - Lechner-Scott, Jeannette; Maltby, Vicky; Lyndon, Amanda; Monif, Mastura; Kilpatrick, Trevor; Butzkueven, Helmut; Taylor, Bruce; McCombe, Pamela; Hodgkinson, Suzanne; Fabis-Pedrini, Marzena; Kermode, Allan; Barnett, Michael; et al.
Abstract : Introduction: Cladribine tablets (marketed as Mavenclad®) is a new oral therapy, which has recently been listed on the pharmaceuticals benefit scheme (PBS) in Australia for treatment of relapsing MS. The current dosing schedule is for 2 courses given a year apart, which has been shown to be effective for treatment of MS up to 4 years in 75% of patients (based on annualised relapse rate). However, re-initiation of therapy after year 4 has not been studied. Methods: This will be a multicentre, 6-year, phase IV, low interventional trial. Subjects considered for treatment with cladribine will receive an initial treatment course in year 1 and a continuing treatment course in year 2. After year 3, patients will have the option for re-dosing, if clinically indicated or to switch to another disease modifying therapy. Throughout the duration of the study we will assess blood based biomarkers including lymphocyte subsets, serum neurofilament light chain, DNA methylation and RNA analysis as well as MRI findings (brain volume/lesion load) and cognitive performance. Results: This study has been approved by the Hunter New England Local Health District Human Research Ethics Committee. The study is due to commence on March 14 th . Conclusions: This will be the first long-term efficacy trial of cladribine which offers re-initiation of therapy after the initial two courses. We expect this study will be an indication if any of the assessed biomarkers can be used to predict treatment efficacy or the need for re-initiation of Cladribine in MS patients.